Framework Meets Reality – A Qualitative Case Study on the Adaptation of Scrum Beyond Software Development - Bäuml, Christof; Sadílek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how Scrum is implemented outside of software development and adapted to diverse organizational and industry-specific conditions. The aim was to identify key patterns of adaptation and to understand their underlying drivers. The methodological basis is a qualitative analysis of four case studies from the fields of marketing, sales, mechanical engineering, and product development. The findings reveal that Scrum was modified in all investigated cases, particularly regarding roles, artifacts, and events. Common adjustments included the delegation of Product Owner responsibilities, the absence of cross-functionality, context-specific changes to backlogs and sprint goals, as well as modified review and planning processes. Successful implementations were observed especially where the Scrum framework was deliberately aligned with organizational structures, cultural contexts, and product requirements. Beyond the analyzed cases, additional factors were identified that can facilitate the introduction process. This study contributes to a deeper understanding of Scrum’s transferability to non-technical domains and demonstrates that the framework can serve as a flexible structure outside of IT when consciously and contextually adapted.
Vedoucí práce: Tomáš Sadílek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses